2002
DOI: 10.1176/appi.ajp.159.6.927
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Prospective Follow-Up of Children With a Prepubertal and Early Adolescent Bipolar Disorder Phenotype

Abstract: The relatively poor outcomes of these subjects may be related to their phenotypic resemblance to severely ill adults with bipolar disorder who have mixed mania, continuous rapid cycling, psychosis, and treatment-resistant psychopathology. A lower level of effectiveness of mood stabilizers in children cannot be ruled out. Although the significance of maternal warmth as a predictor is consistent with reports in adult mania, the significance of intact family as a predictor may be unique to childhood mania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
193
3
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(230 citation statements)
references
References 39 publications
21
193
3
13
Order By: Relevance
“…59 Several reports have described atypical mania-like symptoms in young children. [60][61][62][63][64] Geller and colleagues published the first prospective follow-up study of prepubertal children diagnosed with mania. 63 The baseline intake episode of mania represented the first manic episode for over 80% of the sample.…”
Section: Follow-up Studies Of Clinical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Several reports have described atypical mania-like symptoms in young children. [60][61][62][63][64] Geller and colleagues published the first prospective follow-up study of prepubertal children diagnosed with mania. 63 The baseline intake episode of mania represented the first manic episode for over 80% of the sample.…”
Section: Follow-up Studies Of Clinical Samplesmentioning
confidence: 99%
“…[65][66][67] Researchers describing samples of chronically ill very young children with psychotic features, agitation, irritability, labile mood, impulse-control difficulties, cognitive deficits, and major impairment in functioning have concluded that these children exhibit a subform of mania, or pediatric mania. 34,[62][63][64]68,69 The manic diagnostic decision appears heavily weighted on persistent and pervasive irritability and chronic overactivity. It is difficult to interpret what these children actually suffer from.…”
Section: Follow-up Studies Of Clinical Samplesmentioning
confidence: 99%
“…For instance, two ongoing multisite, National Institute of Mental Health (NIMH) funded studies show that children and adolescents with BPD maintain a functionally impaired status characterized by a highly relapsing and remitting course , Birmaher, 2004, Geller, et al, 2006, Geller, et al, 2004. BPD is a substantial cause of psychiatric morbidity among youth including high rates of hospitalization, disruption of the family environment, and psychosocial disability (Akiskal, et al, 1985, Geller, et al, 2002a, Weller, et al, 1995, West, et al, 1996, Wozniak, et al, 1993.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 115 children with bipolar disorder who were followed up annually over 8 years until they reached adulthood, Geller et al [21,89] found that low ratings of maternal warmth by children and parents predicted relapses into manic episodes and longer manic episodes. The family also had a protective influence in that children who lived with both of their parents had briefer manic episodes than children living in one-parent families.…”
Section: Family Characteristicsmentioning
confidence: 99%